2018
DOI: 10.1177/1457496918798208
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Complications following Introduction of Radical Surgery for Colon Cancer: A Consecutive Patient Series

Abstract: Severe complications following the introduction of complete mesocolic excision are patient dependent and related to open surgery. Patients selected for laparoscopy had less number of complications; therefore, introducing complete mesocolic excision by laparoscopy is justified. Identification of these factors can improve selection of appropriate surgical approach and postoperative patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
3
6
1
Order By: Relevance
“…There were several important observations of this study. Firstly, we found that male patients were at higher risk of severe complications after laparoscopic surgery for T3 or T4 rectal cancer than female patients, which was in line with previous studies [ 12 14 ]. Saadat et al reported that male gender and chronic pulmonary diseases contributed to reoperation after surgery for rectal cancer [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…There were several important observations of this study. Firstly, we found that male patients were at higher risk of severe complications after laparoscopic surgery for T3 or T4 rectal cancer than female patients, which was in line with previous studies [ 12 14 ]. Saadat et al reported that male gender and chronic pulmonary diseases contributed to reoperation after surgery for rectal cancer [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…Severe complications were more common in patients who had increased preoperative hospitalizations and who lived in nursing homes. These findings support recent studies from Norway and Japan [32,33] emphasizing the importance of preoperative evaluation of patient's physical and cognitive performance, to prevent complications in colon cancer surgery. In Finland, aged people move to nursing homes when they cannot survive with maximal help at home and most of them have some degree of cognitive impairment.…”
Section: Discussionsupporting
confidence: 89%
“…Increased morbidity has been reported early in the learning curve of surgeons converting to CME. 36,37 It becomes evident that implementation of CME and, in particular, SILS CME should be under supervision.…”
Section: Discussionmentioning
confidence: 99%